Regulation of Adrenal Steroidogenesis by the High-affinity Phosphodiesterase 8 Family - Tsai, L-C. L.; Beavo, J. A. (Hormone and Metabolic Research, 2012)
The main function of cyclic AMP phosphodiesterases (PDEs) is to degrade cAMP, a ubiquitous second messenger. Therefore, PDEs can function as prime regulators of cAMP/PKA-dependent processes such as steroidogenesis. Until recently, the roles of the PDE8 family have been largely unexplored, presumably due to the lack of a selective inhibitor. This review focuses on recent reports about the regulatory roles of the PDE8 family in adrenal steroidogenesis, as well as the inhibitory properties and specificity of a new PDE8-selective inhibitor, PF-04957325. We also describe a method of measuring urinary corticosterone levels in vivo as a minimally invasive way of monitoring the stress level in a mouse.
Keywords: adrenal cortex; glucocorticoids; androgen